2013
DOI: 10.1136/bcr-2013-009117
|View full text |Cite
|
Sign up to set email alerts
|

Vanishing kidney disease

Abstract: DESCRIPTIONA 60-year-old woman with a known case of diabetes mellitus for last 25 years, presented to our emergency department with symptoms of severe colicky pain in the right lumbar region and paraumbilical region of abdomen and recurrent episodes of vomiting the day before admission. Her family doctor recently moved her on to insulin as her blood sugar was not being controlled by oral antidiabetics. Systemic examination was normal except for severe tenderness in right lumbar and paraumblical regions. Random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Harrabi et al reported a 64-yearold woman with EPN complicated with diabetic ketoacidosis who died of septic shock without surgical drainage [6]. However, another patient with EPN with diabetic ketoacidosis who underwent percutaneous renal drainage combined with antibiotics died 7 days after admission [9]; Unlike our patient, according to CT, this patient belongs to class 3A EPN. Recently, it has been reported that EPN with diabetic ketoacidosis in the patient with allogeneic renal transplantation improved after conservative treatment with intravenous antibiotics without percutaneous drainage or nephrectomy [10]; But our patient is different from this successful case in that there are urinary tract obstruction factors such as right kidney stone and right ureteral stone, and percutaneous drainage is more important in the treatment.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Harrabi et al reported a 64-yearold woman with EPN complicated with diabetic ketoacidosis who died of septic shock without surgical drainage [6]. However, another patient with EPN with diabetic ketoacidosis who underwent percutaneous renal drainage combined with antibiotics died 7 days after admission [9]; Unlike our patient, according to CT, this patient belongs to class 3A EPN. Recently, it has been reported that EPN with diabetic ketoacidosis in the patient with allogeneic renal transplantation improved after conservative treatment with intravenous antibiotics without percutaneous drainage or nephrectomy [10]; But our patient is different from this successful case in that there are urinary tract obstruction factors such as right kidney stone and right ureteral stone, and percutaneous drainage is more important in the treatment.…”
Section: Discussionmentioning
confidence: 61%
“…At present, EPN with diabetic ketoacidosis is rare, only a few cases have been reported [6][7][8][9][10]. And diabetic ketoacidosis is an important predictor of death in patients with EPN [11].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the term "the sign of the deaf kidney" or "vanishing kidney disease" has already been used in the radiology jargon for an ultrasonographic finding of emphysematous pyelonephritis, which happens due to the infiltration of the perirenal environment by gas envelope rather than the complete disappearance of the kidney parenchyma. 15…”
mentioning
confidence: 99%